Independence of the Lawyer in the Anti-Money Laundering Regulation: Reporting Obligation as a Challenge to Constitutional Rights - Joksta, Sandra (Teisė, 2025)
The profession of a lawyer serves as a bridge between the state’s judicial system and the public’s right to a fair trial. This article is devoted to an analysis of the interaction of the principle of independence of bar with the obligation to report suspicious transactions, as provided for in Anti-Money Laundering (AML) regulation, resulting in the fundamental rights being affected. The article raises the following research question: Does the introduction of such a control mechanism not contradict the constitutional principles of the autonomy of the bar, professional secrecy and independence on the one hand and the fundamental rights of the client, on the other hand? The following main conclusions can be drawn: 1. EU law and case law of the ECHR allows to apply AML/CFT requirements towards lawyers only upon condition that their defence functions are not violated. 2. Latvian regulatory framework does not always differentiate clearly enough between activities of a lawyer related to the defence of a client and those in which the lawyer may be subject to AML monitoring mechanisms. 3. An excessively broad interpretation of the reporting duty of lawyers undermines the individual’s trust in the legal profession and may contribute to restrictions of the right to a fair trial.